Online patient feedback is positive, but not used effectively. (23rd March 2020) - Cook, Rob; Davidson, Peter; White, Alicia
The study: Powell J, Atherton H, Williams V, et al. Using online patient feedback to improve NHS services: the INQUIRE multimethod study. Health Serv Deliv Res 2019;7:38. This project was funded by the NIHR Health Services and Delivery Research programme (project number HS&DR 14/04/48). To read the full NIHR Signal, go to: https://discover.dc.nihr.ac.uk/content/signal-000861/online-patient-feedback-is-mostly-positive-but-is-not-being-used-effectively